Optimasi Kualitas Jaringan WIFI Fakultas Melalui Redesain Topologi Dengan Menggunakan Network Simulator 2 - M. Saski; Iwan Iskandar; Novriyanto; Pizaini (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The utilization of WiFi internet networks on campus as tools to support the learning process at the Faculty of Science and Technology is crucial. Therefore, it essential for the campus to provide internet facilities ensure that all activities, including services and the learning process, are effective. This research analyze the quality of WiFi networks at Faculty of Science and Technology using the Quality of Service (QoS) method with parameters such  throughput, delay, packet loss, and jitter. In this study, testing was conducted on WiFi networks in three buildings within the Faculty of Science and Technology, under different conditions during peak hours and off-peak hours, using several SSIDs such as Pegawai, Pimpinan, Uinsuska, Labor TIF dan Baru Belajar, with bandwidths of up to 100Mbps. Test results indicate that the values obtained for throughput, delay, packet loss, and jitter in the three buildings were categorized as "Excellent" with an index of 4. However, in the Lab building, some parameters were found to be low. Therefore, this research conducted a redesign of the topology in the Lab building using Network Simulator 2 (NS2) to improve the quality of the WiFi network. Four nodes were recommended for each floor of the Lab building in the topology redesign. The results of these tests provided QoS parameter values that were used as information for the tested topology recommendations, showing good parameter quality with a throughput value 4738.7 Kbps, a packet loss value 0%, delay value 3.9639249 ms, and jitter value 0,381779103 ms. The results of this testing can be used as information and analystt for the campus PTIPD to enhance the quality of WiFi networks in the Faculty of Science and Technology